Thursday

July 31, 2014

July 31, 2014

Posted by **p** on Thursday, November 5, 2009 at 4:05pm.

6-15x+20=-49

11-15x=-49

11-15=-49-49

15x=-98

x=6

- math115 -
**Jenny**, Thursday, November 5, 2009 at 4:20pmu first distribute the -5 to the 3x n negative 4.

so u get 6-15x+20=-49.

u then combine 6 and 20 to get 26.

so u get 26-15x=-49

then u subtra t 26 from buth sides and get: -15x=-75.

then u divide -15 from both sides n x =5.

hope this helped!!

**Related Questions**

math - Solve by elimination 5x+y=2 3x+y=1 This is what I got : 3(5x+y=2) -5(3x+y...

algebra - -15(3+x)=-6x-9 -45-15x=-6x-9 -45-15x+15x=-6x+-15x-9 -45=21x-9 -45=x-9...

Math - f(x)=13x^2 -15x-14 g(x)=15x^3+14x^2-15x+12 find f(3) × f(10) + f(-7) × g(...

Math - f(x)=13x^2 -15x-14 g(x)=15x^3+14x^2-15x+12 find f(3) × f(10) + f(-7) × g(...

math - if y=5x-2, then -3x=? PLEASE EXPLAIN a 5x -6 b 15x-6 c 15x+6 d -15-6 e -...

Math - A stunt pilot is testing a new plane. The equation that models his height...

Math (logarithmic functions) - Those are the only ones I can't seem to resolve. ...

lomas - Right answer? 15(x^2+3x) + 7(x^2+3x) - 5(x^2+3x) 15x^2+45x+7x^2+21x + 5...

algbrea - 3x-5(3x-7)= 2(x+9) + 45 3x-15x+35= 2x+18 +45 -12x + 35 = 2x+63 -12x -...

bobpursly, - Is this correct now after i revised it Multiply. 3xy^2(5xy-4x+6y) ...